ROLE OF ISLAMIC BANKING IN INVESTMENT PROCESS - GLEB L’VOVICH Podvoisky (Мир новой экономики)
The sharp decline in investment in the economy, caused by a number of factors, dictate the need to find additional sources of funding for its development.Thus it is interesting to analyze the principles of construction and function mechanics of the Islamic banking system, the creation of which began with the 60-ies of the last century.During the global economic crisis, Islamic banking system has proved its exceptional reliability and stability.